"Against Frozen Dogmatic Beliefs": An Analysis of Ali Shariati's Revolutionary Thought - Zulfikar, Muhammad (TAJDID, 2020)
This article aims to explore the idea of "against dogmatic beliefs" echoed by Ali Shariati. By using the critical analysis method, this study finds that the concept of Ali Shariati's revolution is based on Islam even though it is not Islam in the sense of a religion that only contains dogmatic teachings. The transformation of the concept of revolution requires the presence of an agent. This is where Ali Shariati gave the term rausyan fikr (enlightened intellectual) as an agent of revolution from the failure of the ulama who sold their religion to the ruling class. Meanwhile, in an effort to mobilize a revolution to destroy the regime of Syah Reza Pahlavi, Ali Shariati carried out massive movements in the form of speeches in academic pulpits and in public pulpits, writing books and in magazines. Ali Shariati's offer of an Islamic-revolutionary (socialist) pattern was finally successfully transformed into the foundation of the Iranian revolutionary movement.